The collective source. (Snippets from the front.) (Scraps from the war and the post-war.) - Guereña, Jean-Louis (Historia y Memoria de la Educación, 2019)
In this documentary text we reproduce part of the diary titled The Collective Source, written by Juan Luis Guereña. The writings of the young official stretch from 22 May, 1938, when he was in Igualada anticipating the launch of the republican offensive of the Ebro, until 23 September, 1940, when he was in France, having been at several concentration camps for Spanish refugees. The fragments transcribed correspond to the Battle of the Ebro (25 July, 1938 until 16 November, 1938), the retreat, the crossing into France (9 February, 1939), the concentration camps and those involving life in exile in France.